Prevalence of multi-drug resistant bacteria in intensive care units at Tripoli University Hospital, Tripoli, Libya - Khaled Ibrahim; Dalal Thwood; Hajer ELgheriani; Mohamed Salem; Zaynab Elgadiym; Ahmed Zaghdani; Inas Alhudiri; Abdulraouf Habibi; Abdurrezagh Elfahem; Saadeddin Belaid; Otman Ermithi; Mahmoud Almaghrabi; et al. (Libyan Journal of Medicine)
Among hospitalized patients worldwide, infections caused by multidrug-resistant (MDR) bacteria are a major cause of morbidity and mortality. This study aimed to isolate MDR bacteria from five intensive care units (ICUs) at Tripoli University Hospital (TUH). A prospective cross-sectional study was conducted over a seven-month period (September 2022 to March 2023) across five ICUs at TUH. A total of 197 swabs were collected from Patients’, healthcare workers’ and ICUs equipment. Samples collected from patients were nasal swabs, oral cavity swabs, hand swabs, sputum specimens, skin swabs, umbilical venous catheter swabs, and around cannula. Swabs collected from health care workers were nasal swabs, whereas ICUs equipment’s samples were from endotracheal tubes, oxygen masks, and neonatal incubators. Identification and antimicrobial susceptibility test was confirmed by using MicroScan auto SCAN 4 (Beckman Coulter). The most frequent strains were Gram negative bacilli 113 (57.4%) with the predominance of Acinetobacter baumannii 50/113 (44%) followed by Klebsiella pneumoniae 44/113 (40%) and Pseudomonas aeruginosa 6/113 (5.3%). The total Gram positive bacterial strains isolated were 84 (42.6%), coagulase negative Staphylococci 55 (66%) with MDRs (89%) were the most common isolates followed by Staphylococcus aureus 15 (17.8%). Different antibiotics were used against these isolates; Gram- negative isolates showed high resistance rates to ceftazidime, gentamicin, amikacin and ertapenem. A. baumannii were the most frequent MDROs (94%), and the highest resistance rates in Gram-positive strains were observed toward ampicillin, oxacillin, ampicillin/sulbactam and Cefoxitin, representing 90% of total MDR Gram-positive isolates. ESBL and MRS were identified in most of strains. The prevalence of antibiotic resistance was high for both Gram negative and Gram positive isolates. This prevalence requires strict infection prevention and control intervention, continuous monitoring, implementation of effective antibiotic stewardship, immediate, concerted and collaborative action to monitor its prevalence and spread in the hospital.